The Global Water Partnership - Independent Evaluation Group (Washington, DC: World Bank, 2017)
The Global Water Partnership (GWP) was established by the Swedish International Development Agency (SIDA), the United Nations Development Program (UNDP), and the World Bank in 1996 in response to international concern about deteriorating freshwater resources. The initial mission of the GWP was to 'support countries in the sustainable management of their water resources' by means of an advocacy network based on the principles of integrated water resources management (IWRM). Its initial objectives were: 1) to clearly establish the principles of sustainable water resources management; 2) to identify gaps and stimulate partners to meet critical needs within their available human and financial resources; 3) to support action at the local, national, regional, or river basin level that follows the principles of sustainable water resources management; and 4) to help match needs to available resources. The GWP was chosen for a Global Program Review (GPR) because it provides lessons for the design and operation of advocacy networks for water-related activities in member countries. Because the governance and management of the GWP changed hands in 2008, the findings of this review do not reflect on the current governance and management of the partnership.